2013
DOI: 10.1177/1535370213482442
|View full text |Cite
|
Sign up to set email alerts
|

Directed neural differentiation of induced pluripotent stem cells from non-human primates

Abstract: Induced pluripotent stem cells (iPS cells) are important for the future development of regenerative medicine involving autologous cell therapy. Before autologous cell therapy can be applied to human patients, suitable animal models must be developed, and in this context nonhuman primate models are critical. We previously characterized several lines of marmoset iPS cells derived from newborn skin fibroblasts. In the present studies, we explored methods for the directed differentiation of marmoset iPS cells in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The clone that we was used in iterative process of improving differentiation (B8; Farnsworth et al, 2013) responded as expected, with increases of up to 100-fold in the tested genes. However, two other clones (88, 15) that were previously validated as iPS cells via teratoma formation (Wu et al, 2010), responded much less well (up to about 8-fold, but also failing to respond at all in some cases).…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…The clone that we was used in iterative process of improving differentiation (B8; Farnsworth et al, 2013) responded as expected, with increases of up to 100-fold in the tested genes. However, two other clones (88, 15) that were previously validated as iPS cells via teratoma formation (Wu et al, 2010), responded much less well (up to about 8-fold, but also failing to respond at all in some cases).…”
Section: Resultssupporting
confidence: 62%
“…We investigated how well different marmoset iPS cell clones responded to a previously developed directed differentiation protocol (Farnsworth et al, 2013). In this protocol, the cells are formed into aggregates in hanging-drop plates for 3 days and then exposed to differentiation factors (dual SMAD inhibitors plus retinoic acid) for 3 days in monolayer culture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, specific culture conditions have been developed to maintain the pluripotent stem cells (PSCs) in an extended PSC stage (EPSC) with widespread chimeric contribution to embryonic and extraembryonic lineages in vivo [ 28 ]. The derivation and tendency of the marmoset pluripotent stem cells to differentiate into neural lineages has been reported [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] using variable techniques for the neuralization based on the initial protocol developed for human embryonic stem cells [ 38 , 39 , 40 , 41 , 42 , 43 ]. In this study, we demonstrated that using the NN1 medium supplemented with growth factors, we were able to isolate NSCs that are responsive to mitogenic growth factor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, three novel marmoset ESC lines have been derived from the natural morula stage of preimplantation embryos, and one novel male ESC line has been derived from the expanded blastocyst stage (Debowski et al 2016). Marmoset iPSCs from fetal liver cells and adult fibroblasts have also been reported (Tomioka et al 2010; Farnsworth et al 2013; Qiu et al 2015; Vermilyea et al 2017). The capacity of marmoset ESC and iPSC lines to differentiate into cardiomyocytes and hematopoietic cells by induction has been demonstrated (Sasaki et al 2005; Tomioka et al 2010).…”
Section: Discussionmentioning
confidence: 99%